Simulation of wakefields excited by a train of electron bunches in rectangular dielectric waveguide - Onishchenko, N.I.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2005)
Wake field excitation by a sequence of electron bunches in rectangular dielectric waveguide of finite length is investigated for acceleration with high gradient electric field. Characteristics of wake field for parameters of planned in NSC KIPT experiments are determined. Досліджені процеси збудження кільватерного поля електронними згустками та їх послідовністю в прямокутних діелектричних хвилеводах скінченої довжини: напів обмеженого хвилеводу та резонаторі. Визначені характеристики кільватерного поля для параметрів запланованого в ННЦ ХФТІ експерименту Исследовано возбуждение кильватерного поля электронными сгустками и их последовательностью в прямоугольных диэлектрических волноводах конечной длины: полу бесконечном волноводе и резонаторе. Определены характеристики кильватерного поля для параметров планируемого в ННЦ ХФТИ эксперимента.